Dynamic obstacle avoidance approach for car-like robots in dynamic environments - Mohd. Sani, Mohamad Hashim; Tien-Fu, Lu; Hassrizal, Hassan Basri (Institute of Electrical and Electronic Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/